Developing Business Application Systems On the Specification and Selection of Software Components and Services - Skroch, Oliver; SpringerLink (Online service) (Wiesbaden : Gabler Verlag, 2010)
The prosperity of many businesses and institutions is strongly related to a high quality, cost-effective and fast development of application software. Oliver Skroch argues that the reuse of components and services counts among the few fundamental and most promising approaches when pursuing these objectives. He presents research results related to strategic, tactic, and operational ranges of consideration in component- and service-oriented software development.
Strategic framework -- A theory of software reuse strategies in ideal type stable and turbulent market environments -- Integration assessment ofan individually developed application vs. software packages from the market - an experience report -- Specification -- The importance of requirements specifications for successful IT projects -- A method to evaluate the suitability of requirements specifications for offshore projects -- Selection -- Optimal stopping for the run-time self-adaptation of software systems -- Reducing domain level scenarios to test component-based software -- Conclusions and outlook.
Keywords: Economics; Management information systems; Economics/Management Science; Business Information Systems